Maceral types and quality of coal in the Tuli Coalfield : a case study of coal in the Madzaringwe Formation in the Vele Colliery, Limpopo Province, South Africa - Denge, Elelwani; Baiyegunhi, Christopher (MDPI, 2021)
The Madzaringwe Formation in the Vele colliery is one of the coal-bearing Late Palaeozoic units of the Karoo Supergroup, consisting of shale with thin coal seams and sandstones. Maceral group analysis was conducted on seven representative coal samples collected from three existing boreholes—OV125149, OV125156, and OV125160—in the Vele colliery to determine the coal rank and other intrinsic characteristics of the coal. The petrographic characterization revealed that vitrinite is the dominant maceral group in the coals, representing up to 81–92 vol.% (mmf) of the total sample. Collotellinite is the dominant vitrinite maceral, with a total count varying between 52.4 vol.% (mmf) and 74.9 vol.% (mmf), followed by corpogelinite, collodetrinite, tellinite, and pseudovitrinite with a count ranging between 0.8 and 19.4 vol.% (mmf), 1.5 and 17.5 vol.% (mmf), 0.8 and 6.5 vol.% (mmf) and 0.3 and 5.9 vol.% (mmf), respectively. The dominance of collotellinite gives a clear indication that the coals are derived from the parenchymatous and woody tissues of roots, stems, and leaves. The mean random vitrinite reflectance values range between 0.75% and 0.76%, placing the coals in the medium rank category (also known as the high volatile bituminous coal) based on the Coal Classification of the Economic Commission for Europe (UN-ECE) coal classification scheme. The inertinite content is low, ranging between 4 and 16 vol.% (mmf), and it is dominated by fusinite with count of about 1–7 vol.% (mmf). The high amount of inertinite, especially fusinite, with empty cells and semi-fusinite in the coals will pose a threat to coal mining because it aids the formation of dust.
Journal article published in the journal of Applied Sciences
Keywords: Coal; Maceral; Quality; Madzaringwe Formation; Tuli Coalfield; Coal -- Analysis; Coal; Maceral; Coalfields -- South Africa